Unlocking the Potential of Biomass Energy in Pakistan - Saghir, Muhammad; Zafar, Shagufta; Tahir, Amiza; Ouadi, Miloud; Siddique, Beenish; Hornung, Andreas (Frontiers in Energy Research, 2019)
Being a developing economy, Pakistan is facing a severe energy crisis that limits its economic development. Pakistan relies heavily on energy resources like natural gas, oil, hydropower, nuclear, coal and liquefied petroleum gas (LPG) which contribute as 48.3, 32.1, 11.3, 7.6, and 0.6% of the primary energy supply, respectively. Because of the rapidly growing population and economy, Pakistan's energy needs are huge; to accomplish these energy necessities, Pakistan is continually spending 7–9 billion on the import of fossil fuels. To resolve the serious issues of energy availability, the Alternative Energy Development Board (AEDB) of Pakistan is currently exploring the development of renewable energy technologies in Pakistan that will be beneficial for the developing economy so that Pakistan might be able to minimize the growing energy crisis. Out of all the renewable energy resources, biomass is considered the best and most easily accessible source of energy with its unique environmentally friendly nature, constant supply, wider availability, and ease of integration into existing infrastructure. Despite the presence of an abundance of biomass energy resources, there is still a need for work on the use of these sources to produce energy. This literature review explores the availability of biomass resources in Pakistan and their potential for addressing rapidly growing energy demand in the country, which can assist in the stabilization of a Pakistan's energy demand for challenged economic development.